A short history of the Ismailis : traditions of a Muslim community - Daftary, Farhad (Islamic surveys., 1998)
Despite being one of the key Shi'i Muslim communities, the Ismailis were until recently studied primarily on the basis of the accounts of their enemies. This new introduction is the first to be based on modern scholarship, taking account of recently recovered Ismaili texts. It covers all the main developments in the major phases of Ismaili history, from the early formative period, through the Fatamid golden age and the Alamut and post-Alamut periods, to more recent history. Dealing only with the most important historical developments, this is a comprehensive and accessible survey for all newcomers to the subject."